2014
DOI: 10.1177/0004563214534636
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of limits for significant unidirectional changes in two or more serial results of a biomarker based on a computer simulation model

Abstract: Background: Reference change values (RCVs) were introduced more than 30 years ago and provide objective tools for assessment of the significance of differences in two consecutive results from an individual. However, in practice, more results are usually available for monitoring, and using the RCV concept on more than two results will increase the number of false-positive results. Therefore, a simple method is needed to interpret the significance of a difference when all available serial biomarker results are c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 11 publications
1
36
0
Order By: Relevance
“…As also previously found 9 we have shown that the practical use of traditional RCV calculations applied on normally distributed data will produce too many false positive results especially for high values of CV T , compared to theoretical RCV calculations. On the other hand, the calculated RCF up factors are comparable for both normal and ln-normal distributions up to CV T ¼ 20.0% (Table 1), but not for RCF down factors The RCF down factor is < 0 (negative) and therefore the significant limit is zero (0) because a negative concentration makes no sense.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…As also previously found 9 we have shown that the practical use of traditional RCV calculations applied on normally distributed data will produce too many false positive results especially for high values of CV T , compared to theoretical RCV calculations. On the other hand, the calculated RCF up factors are comparable for both normal and ln-normal distributions up to CV T ¼ 20.0% (Table 1), but not for RCF down factors The RCF down factor is < 0 (negative) and therefore the significant limit is zero (0) because a negative concentration makes no sense.…”
Section: Discussionsupporting
confidence: 70%
“…The method has been described in detail in a previous publication associated with significant unidirectional changes in serial results. 9 Briefly, the method is described here with the modifications associated with significant bidirectional changes in serial results.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[6]. Several manuscripts can be found in this field, for example [3,[9][10][11]. The approach defines criteria for normal variation in two sequential measurements, which mathematically are often defined as…”
Section: Introductionmentioning
confidence: 99%
“…[6]. Several manuscripts can be found in this field, for example [3,[9][10][11]. The approach defines criteria for normal variation in two sequential measurements, which mathematically are often defined as The calculation of RCVs for many different laboratory outcomes is quite simple since all laboratories know approximately the analytical and intra-individual variabilities for medical laboratory results from samples from the healthy population.…”
mentioning
confidence: 99%